2002
DOI: 10.1034/j.1399-3038.2002.00010.x
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin A status in children with asthma

Abstract: Low vitamin A levels have been found in a number of diseases in children. The aim of this study was to examine the vitamin A status in children with asthma and to correlate the changes with severity of disease. Serum levels of vitamin A, retinol-binding protein (RBP), and albumin were estimated in 35 asthmatic children (24 males) in the age group of 2-12 years (mean 5.89 years) and 29 controls (19 males). Both study and control groups were similar with respect to age, sex, and overall nutritional status. Twent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
58
2
4

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(66 citation statements)
references
References 14 publications
2
58
2
4
Order By: Relevance
“…Additionally, vitamin A includes features such as anti-inflammatory, antiinfective and antioxidant effects. [11,12] As a consequence of increasing number of cells during the repair of damaged tissues and continuing inflammation, a lack of vitamin A may occur. [13] On respiratory syncytial virus and measles infections, there is evidence of lack of vitamin A.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Additionally, vitamin A includes features such as anti-inflammatory, antiinfective and antioxidant effects. [11,12] As a consequence of increasing number of cells during the repair of damaged tissues and continuing inflammation, a lack of vitamin A may occur. [13] On respiratory syncytial virus and measles infections, there is evidence of lack of vitamin A.…”
Section: Discussionmentioning
confidence: 99%
“…[12,15,16] There are also several studies exhibiting normal vitamin A levels and some others exhibiting low vitamin A levels. [11,12,15,16] Kompauer et al [17] showed low vitamin A level in the adults with AR. According to the literature search of the last ten years on children, there is no study on the relationship between AR and vitamin A level.…”
Section: Discussionmentioning
confidence: 99%
“…Bu nedenle, üst solunum yollarında A vitamini düzeyinin eksikliği mukus ve bazal hücrelerin ço-ğalmasını azaltmaktadır. 12 Vitamin; karaciğer ile organ etleri, yağlar, yumurta, balık ve sütte bulunduğu için astım durumunda bu besinleri yeterli miktarda tüketmeye özen gösterilmelidir. 13 Yapı-lan bir çalışmada, astım hastası çocukların serum A vitamini düzeylerinin kontrol grubuna göre daha düşük olduğu gösterilmiştir.…”
Section: Anti̇oksi̇danlarunclassified
“…11 Astımı olan çocuk-larda serum A vitamini düzeyini araştıran başka bir çalışmada, 35 astım hastası ve 29 sağlıklı çocuğun serum A vitamini düzeylerine bakılmış ve astımı olan çocukların serum A vitamini düzeylerinin sağ-lıklı çocuklarınkinden önemli düzeyde düşük olduğu saptanmıştır. 12 …”
Section: Anti̇oksi̇danlarunclassified
“…: retinol binding protein -RBP); high consumption of antioxidants, due to the exacerbation of oxidative stress caused by inflammation and infection; and increase in urinary excretion during the acute phase of infection. 9,10 In the literature, there is some controversy over the clinical effects of low serum concentrations of vitamin A, observed in the acute phase of the infectious process. Studies show that the transient reduction, associated with the acute phase of the infectious process, in serum retinol levels, can combine with retinol stores in the eye and lead to night blindness and retinal dystrophy.…”
Section: Introductionmentioning
confidence: 99%